FAKTOR-FAKTOR PENENTU TURNOVER INTENTION PEGAWAI BANK: PERAN WORK-LIFE BALANCE, STRES KERJA, KOMPENSASI, DAN KEPUASAN KERJA - Mochamad Syafruddin Aji; Ronny; Tanza Dona Pertiwi; Muhammad Cholil (Management and Sustainable Development Journal, 2025)
The high employee turnover in Indonesia’s banking sector in recent years reflects intense pressure and demanding performance targets that may disrupt employees’ work-life balance and job satisfaction. This study aims to analyze the factors influencing bank employees’ turnover intention by examining the roles of work-life balance, job stress, and compensation, as well as testing job satisfaction as a mediating variable. A quantitative approach was employed through a survey of 104 bank employees in East Java, and the data were analyzed using SEM-PLS. The findings reveal that work-life balance and job stress have a significant effect on turnover intention, whereas compensation and job satisfaction show no significant effect. Moreover, job satisfaction does not mediate the effects of work-life balance, job stress, or compensation on turnover intention. These results indicate that in a target-driven banking industry, reducing turnover intention cannot be achieved merely by increasing compensation or relying on job satisfaction. The practical implications suggest that management should design more human-centered policies, such as setting realistic targets, monitoring workload, implementing flexible work arrangements, and establishing structured stress management programs. These efforts are essential to create a more supportive work environment that enables employees to maintain role balance without compromising performance, ultimately reducing their intention to leave the organization.